كروماتوغرافيا الغاز – مطيافية الكتلة GC-Mass استخالص بعض المواد العضوية في نبات القريص وتشخيصها بتقنية - عبد الله زينب محمود; وادي امل ناجي; دحام هادي كريم (Al-Nahrain Journal of Science, 2013)
The Research contained preparation of Urtica dioica (extraction of temperature 40C˚). alcoholic extract was examine by infrared spectroscopy FT-IR, UV spectroscopy and gas chromatography- mass spectrometry technique to characterize the active materials substances such as organic acids and organic materials Nitrogenic base, and test the ability of inhibition for alcoholic extract on some bacteria Pseudomones aeruginosa, Staph aurens which caused skin diseases.